2020
DOI: 10.7759/cureus.8379
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Leaks and Pseudomeningocele after Posterior Fossa Surgery: Effect of an Autospray Dural Sealant

Abstract: BackgroundPosterior fossa craniotomies can be complicated by cerebrospinal fluid (CSF) leaks, infection, meningitis, neurologic deficits, and intracranial hypotension caused by defective closure of the dura. Secondary dural closures such as pericranial graft, muscle graft, glue, sealants, or fat graft are used. However, there have been few studies examining the use of sealants with a polyethylene glycol and polyethylenimine component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Lee et al reported a 27.0% combined incidence of CSF leak or PMC in their series of 122 patients undergoing posterior fossa surgery. 14 In a series of adult patients with CM-I undergoing PFD with duraplasty, Almotairi and Tisell reported an 11.5% incidence of any postoperative CSF disturbance and, although their incidence was lower than in the present study, a similar number of their included patients (4/51 [7.8%]) did require permanent CSF diversion. 1 Galan et al reported a 21.8% incidence of either PMC or CSF leak, with a readmission rate of 13%.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Lee et al reported a 27.0% combined incidence of CSF leak or PMC in their series of 122 patients undergoing posterior fossa surgery. 14 In a series of adult patients with CM-I undergoing PFD with duraplasty, Almotairi and Tisell reported an 11.5% incidence of any postoperative CSF disturbance and, although their incidence was lower than in the present study, a similar number of their included patients (4/51 [7.8%]) did require permanent CSF diversion. 1 Galan et al reported a 21.8% incidence of either PMC or CSF leak, with a readmission rate of 13%.…”
Section: Discussioncontrasting
confidence: 60%
“…This is similar to the systematic review by Kinaci et al and the more recent, single-institution experience of Lee et al, neither of whom found a significant association between use of a dural sealant and postoperative CSF-related complications. 14,15 In contrast, Galan et al found that fibrin glue dural sealants specifically reduced the risk of postoperative PMC, but they did not find the same association with PEG sealants. 9 Their study, with its larger sample size (n = 165) and greater incidence of postoperative CSF disturbances (41.8% risk of PMC or CSF leak), may have been better powered to detect a difference among dural sealants.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[ 2 ] Lumbar drains (LDs) are second-line therapy for iatrogenic CSF leaks. [ 5 , 7 , 10 ] Understandably, accessing the lumbar space comes with its own set of risks that should be weighed against the benefits of performing the procedure. One of the most common and major risks is CNS infection.…”
Section: Introductionmentioning
confidence: 99%